Angiogenic markers: molecular targets for personalized medicine in pituitary adenoma. (August 2013) - Tanase, Cristiana; Codrici, Elena; Popescu, Ionela Daniela; Cruceru, Maria Linda; Enciu, Ana-Maria; Albulescu, Radu; Ciubotaru, Vasile; Arsene, Dorel
Aim: Pituitary adenomas are typically slow-growing and histologically benign tumors that can occasionally behave in a malignant-like manner, invading adjacent structures or recurring after treatment. Using protein analysis methods and multiplex xMAP assays, we aimed to find out if these particular types of tumors express angiogenic markers VEGF and basic FGF (bFGF), which are associated with tumor growth and invasiveness, and quantify them in order to establish their usefulness as biomarkers.Materials & methods: We have analysed the expression of angiogenic markers VEGF and bFGF in serum and tissue specimens from 66 pituitary adenomas (43 invasive and 23 noninvasive). For serum analysis, we used xMAP and ELISA, and for tissue analysis, we performed histopathology and immunohistochemistry.Results & conclusion: We measured the serum angiogenic factors in pituitary adenomas. The quantification methods revealed significant differences between pituitary adenoma patients and controls, for both VEGF (212.4 vs 112.5 pg/ml in controls) and bFGF (mean value of 12.6 vs 10.8 pg/ml in controls), and also differentiated between invasive and noninvasive adenomas (p < 0.05). The tissue expression of VEGF and bFGF strongly correlated with their serum level increase. Our findings can be further developed into methods for selection of patients suitable for personalized, antiangiogenic therapy.